Skin-protective effects of a zinc oxide-functionalized textile and its relevance for atopic dermatitis - Wieg; C; Hipler U-C; Boldt S; Strehle J; Wollina U (Dove Medical Press, 2013)
Cornelia Wiegand,1 Uta-Christina Hipler,1 Sebastian Boldt,2 Joachim Strehle,2 Uwe Wollina21Department of Dermatology, University Medical Center Jena, Jena, Germany; 2Department of Dermatology and Allergology, Academic Teaching Hospital Dresden-Friedrichstadt, Dresden, GermanyAbstract: Atopic dermatitis (AD) is a chronic inflammatory disease characterized by the impairment of the skin-barrier function, increased oxidative cellular stress, and bacterial colonization. Hence, medical therapies of AD aim to control infection, reduce inflammation, and restore skin-barrier function by use of topical and systemic antibacterial drugs, topical corticosteroids, topical calcineurin inhibitors, and moisturizers. Textiles have the longest and most intense contact with the human skin, and functional textiles with intrinsic properties such as antioxidative capacity and antibacterial activity have been gaining in importance in medical applications. Specially designed textiles may support AD treatment and improve quality of life of AD. Here, we investigated the role of ZnO-functionalized textile fibers in the control of oxidative stress in AD in vitro and in vivo. In addition, the antibacterial effect and biocompatibility of the Zn textile was evaluated in vitro. We observed a rapid improvement of AD severity, pruritus, and subjective sleep quality when AD patients wore the ZnO textiles overnight on 3 consecutive days. This is possibly due to the high antioxidative capacity of the ZnO textile, as well as the allocation of strong antibacterial activity. Moreover, it was shown that the ZnO textiles possess very good biocompatibility and were well tolerated by AD patients.Keywords: atopic dermatitis, antibacterial activity, biocompatibility, functionalized textiles, oxidative stress